SMEs and Bank Lending Relationships: the Impact of Mergers - Hans Degryse; Nancy Masschelein; Janet Mitchell (National Bank of Belgium, 2004)
This paper studies the impact of bank mergers on firm-bank lending relationships using information from individual loan contracts in Belgium. We analyse the effects of bank mergers on the probability of borrowers maintaining their lending relationships and on their ability to continue tapping bank credit. The environment reflects a number of interesting features: high banking sector concentration; "in-market" mergers with large target banks; importance of large banks in providing external finance to SMEs; and low numbers of bank lending relationships maintained by SMEs. We find that bank mergers generate short-term and longer-term effects on borrowers' probability of losing a lending relationship. Mergers also have heterogeneous impacts across borrower types, including borrowers of acquiring and target banks, borrowers of differing size, and borrowers with single versus multiple relationships. Firms borrowing from acquiring banks are less likely to lose their lending relationship, while target bank borrowers are more likely to lose their relationship. Firms borrowing from two of the merging banks are less likely to lose their relationship than firms borrowing from only one of the merging banks or firms borrowing from nonmerging banks.
Keywords: G21; 330; loans; bank mergers; bank relationships; credit register; Bank; Unternehmenskonzentration; Kreditpolitik; Lieferantenmanagement; Kreditrisiko; KMU; Kreditwürdigkeit; Auskunftei; Belgien